2022
DOI: 10.1037/bul0000382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peer observation on risky decision-making in adolescence: A meta-analytic review.

Abstract: Real-world health and crime statistics indicate that adolescents are prone to engage in risks in the presence of peers. Although this effect has been documented in several lab studies, existing evidence varies and the psychological mechanisms that give rise to peer observation-induced shifts in adolescent risky decisionmaking remain poorly understood. We conducted a systematic literature review and meta-analysis to quantify the magnitude of the effect of direct peer observation on risky decision-making in adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 143 publications
1
1
0
Order By: Relevance
“…Instead, we observed the opposite: In our sample, participants actually took fewer risks in the socially rewarding compared to nonsocially rewarding situations. These results are in line with recent work that has begun to identify boundary conditions of the risk-enhancing effect of peers (e.g., Defoe et al, 2020; Somerville et al, 2019; see also Chung et al, 2020, and Powers et al, 2022, for a meta-analysis). This difference might be explained by a desire of young people to protect people socially close to them, as opposed to infecting them per DS theory.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, we observed the opposite: In our sample, participants actually took fewer risks in the socially rewarding compared to nonsocially rewarding situations. These results are in line with recent work that has begun to identify boundary conditions of the risk-enhancing effect of peers (e.g., Defoe et al, 2020; Somerville et al, 2019; see also Chung et al, 2020, and Powers et al, 2022, for a meta-analysis). This difference might be explained by a desire of young people to protect people socially close to them, as opposed to infecting them per DS theory.…”
Section: Discussionsupporting
confidence: 90%
“…Second, adolescents’ motivation to achieve certain goals and engage in certain behaviors can be strongly influenced by behaviors that are approved or sanctioned by peers. Research has shown that in some contexts the mere presence of peers, especially high-status peers, can alter adolescents’ motivation to engage in risk-taking, antisocial, and prosocial behaviors ( Powers et al, 2022 , Somerville et al, 2019 ). Importantly, young adults are not passively exposed to their peer influence but can actively select whom to spend time with.…”
Section: Novel Direction 2: Bringing Social Network As a Research Goa...mentioning
confidence: 99%
“…From purchasing a car to getting engaged, important life decisions are often made in social contexts, whether around strangers or loved ones. Social influence can dramatically shape attitudes towards reward-related decision-making (Dennison et al, 2022; Fareri et al, 2012; Powers et al, 2022), including maladaptive choices (O’Brien et al, 2011). Neural reward valuation is also dependent upon individual differences in trait sensitivity to rewards (Chat et al, 2022; Scult et al, 2016).…”
Section: Introductionmentioning
confidence: 99%